Предмет: Математика,
автор: egop2005
решите уравнение 2х-(6х+1)=9
Ответы
Автор ответа:
3
2х-(6х+1) = 9
2х-6х-1 = 9
-4х = 9+1
-4х = 10
-х = 10:4
-х = 2.5
х = -2.5
Проверка:
2×(-2.5)-(6×(-2.5)+1)=9
-5-(-15+1)=9
-5-(-14)=9
-5+14=9
9=9
2х-6х-1 = 9
-4х = 9+1
-4х = 10
-х = 10:4
-х = 2.5
х = -2.5
Проверка:
2×(-2.5)-(6×(-2.5)+1)=9
-5-(-15+1)=9
-5-(-14)=9
-5+14=9
9=9
Аноним:
-5=9
Похожие вопросы
Предмет: Физика,
автор: alinakond235
Предмет: Английский язык,
автор: jokggh139
Предмет: Английский язык,
автор: proqramyuklemek1
Предмет: Физика,
автор: Anna6839